PENGARUH KAPASITAS SUMBER DAYA MANUSIA PENYULUH TERHADAP KINERJA PENYULUH PERTANIAN DI KOTA KENDARI - Sallahuddin Salahuddin; Nurhayu Malik (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to describe the capacity of human resources of extension workers in Kendari City. This study was conducted in Kendari City in April - June 2024. Sampling in this study was carried out using the census method. In this study, the entire research population, namely agricultural extension workers with the status of State Civil Apparatus (ASN) in Kendari City, totaling 50 people, were all taken as research samples. The research variables are the capacity of human resources of extension workers in this study including: communication skills, attitudes, knowledge, mastery of technical aspects of innovation, and work ethics. The data obtained were analyzed descriptively quantitatively. The results of the study showed that the capacity of human resources of extension workers in Kendari City was in the very good category. Agricultural extension workers in Kendari City have implemented all dimensions of human resource capacity